Cross-Sectional Analysis of Immunohistochemical Expression of Mismatch Repair Proteins in Prostate Cancer - Khalil, Muhammad Atif; Zafar, Nadeem; Tariq, Hassan; Khan, Wajahat Ahmed; Zafar, Moniba; Qurni, Muhammad Owais; Ahmed, Siyab (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the immunohistochemistry-based frequency of mismatch repair protein (MSH-2, MSH-6, MLH-1 & PMS-2) deficiency in prostate cancer.Study Design: Cross-sectional study.Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from Jan 2021 to Jul 2022.Methodology: The characteristics and clinical data of 82 prostatic cancer patients who had transurethral resection of the prostate and surgical resections were examined. MLH-1, MSH-2, PMS-2, and MSH-6 antibodies were utilized during immune-histochemical staining. The status of each patient's mismatch repair deficit was established once the results were assessed.Results: In the study, mean age of presentation was 70.90±8.36 years. Most common histological type was acinar adenocarcinoma, 67(81.70%). Out of 82 patients with prostatic carcinoma, 17(20.73%) patients had lost their immunohistochemistry staining for MMR proteins. Nonetheless, no mismatch repair deficit was found in the 65(79.27%) remaining instances. One patient had a simultaneous loss of all four antibodies, two had loss of MLH-1, three had loss of MSH-2, eleven had loss of PMS-2, and twelve had loss of MSH-6.Conclusion: The frequency of mismatch repair deficiency in our community's prostate cancer patients was reported to be 34.1%, which may be utilized as a base for genetic testing to track the effectiveness of treatment and forecast the overall survival rate for patients with prostate cancer. Studies are also needed to explain the MMR protein’s genetic role in cancer formation, together with the signaling pathway.